Peluasan Bandaraya Metropolitan Jakarta dan impaknya terhadap gunatanah dan corak pekerjaan penduduk pinggiran: Kes Bandar Baru Bumi Serpong Damai - Ratnawati Yuni Suryandari, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2006)
This article describes occupational change of dwellers due to the conversion of agricultural land to a new town the Bumi Serpong Damai (BSD) at the urban fringe of Jakarta in 2004. The district of Tangerang lies about 20 km to the western part of Jakarta with the sample villages of Lengkong Gudang, Rawabuntu and Pagedangan lying 3km, 6km and 9km respectively from the central place of BSD. From the three sample villages, 10 percent or 256 of the dwellers’ household heads were taken as respondents. The study found that: (1) Before BSD, the area was a mix of agriculture and non-agriculture uses. The number of part time farmers were more than that of full time farmers. About 46.9 percent of the original dwellers owned and worked their subsistence farm land. Those who did not own land worked as small traders and labourers.About 50 percent of the dwellers’ income were below poverty line; (2) After BSD, most dwellers sold their land to BSD making the proportion of non -farmers jump to 82.8 percent; (3) Some 50 percent of theoriginal dwellers still lived below the poverty line. The paper concludes that agricultural land conversion to urban landuse has managed to uplift but not more than 50 per cent of the original dwellers out of poverty.